(untitled) (European Journal of Pure and Applied Mathematics, 2010)
Many researchers investigated the flat Bochner tensor on some kinds of almost Hermitian manifold. In the present paper the author studies this tensor on general class almost Hermitian manifold by using a new methodology which is called an adjoint G-structure space. Thus this study generalize the results which are found out by those researchers. It is proved that if M is an almost Hermitian manifold of class R1 with flat Bochner tensor, then either M is 2-dimensional flat Ricci manifold or n-dimensionalflat scalar curvature tensor manifold. As well, it is proved that if M is an almost Hermitian manifold with flat Bochner tensor, then M is a manifold of class R3 if and only if M is a linear complex manifold. Later on, equivalently of classes R2 and Â R3 is investigated. Finally we prove that if M is flat manifold withÂ flat Bochner tensor, then M is an Einstein manifold with a cosmological constant.Â Â